Turbodrills design and performance analysis for efficient drilling in hard rocks - Mokaramian, A.; Rasouli, Vamegh; Cavanough, G. (WITS, 2012)
The authors have recently proposed Coiled Tube Turbodrilling technology for drilling deep hard rocks mineral exploration. Coiled Tube (CT) is a continuous length of ductile steel or composite tube that itself cannot rotate and therefore a down hole motor is needed to provide mechanical power to the bit. Amongst the down hole motors, turbodrills (turbine down hole motors) are an excellent fit with CT operations for hard rocks, providing a smooth borehole with little vibrational effects during drilling with high output rotational speed. The turbine motor section has multistage of rotors and stators which convert the hydraulic power to mechanical power. This paper presents a methodology for designing turbodrills with asymmetric rotor or stator blades configurations. Here, the turbodrill is designed specifically for small size CT system providing suitable output power and rotation speed with applicable input flow properties. Also, the results of a few numerical simulations carried out using computational fluid dynamics (CFD) code are presented. The results help in choosing the best turbine motor configurations to obtain optimum rotational speed and torque during drilling hard rocks for small hole size exploration applications. Similar methodology can be used to design and choose the best turbodrill for other hard rocks drilling conditions.